Multipolar International System And The Place Of Indonesia: Prospect And Opportunities - Mladenov, Stanislav Vladimirov; Sulthan, Mohamad Fikri (JASSP, 2023)
In human history, the factor of international relations and what system they will develop has always been present. For the last three hundred years, the dynamics in this aspect have been significant until the 90s, which opened the possibility for the first time that the world would be under the control of a hegemonic idea. However, the political practice of the 21st century shows that globalization is facing problems and some countries are looking for an alternative path. The traditions and values resulting from them unite different peoples, nations, and countries in the idea of civilizational cooperation. This study aims to explain the multipolar international system and how civilizations are divided in Indonesia according to Huntington's theory of the Clash of Civilizations and as well as to find out the prospects and opportunities for Indonesia as a country with one of the largest economies in the world. This research uses a qualitative research method with a descriptive approach. The results of this study explain Indonesia's position amid various civilizations which can lead to conflicts in the future.